Party premiums. Material incentives and political participation in Iceland - Ólafur Heiðar Helgason 1992- (2015)
Economics has not provided satisfactory explanations of political participation. Research on the phenomenon tends to emphasize either the irrationality of political activism or the role of non-material incentives. These frameworks are not entirely helpful in explaining the relationship between political parties and the broader economy. This study uses data from the Icelandic National Election Study to examine the income and employment status of party members in the 1983-2013 period in order to gain insight into the role of material incentives in political activism in Iceland. Ordinary regressions are complemented with endogenous switching regressions in order to assess the systematic income and employment differentials between party members and the general population. This wage differential is defined as party premium, and any part of the wage differential which is caused by party membership is defined as real party premium. The study finds that the Icelandic parties differed in the magnitude and the direction of their party premiums in the 1987-2013 period. The Independence Party had a large, positive and increasing income party premium; the Progressive Party had a fluctuating income premium, which was close to zero on average; and the left parties, in particular the Left-Green Movement, had a negative income premium over the period. Potential causes of party premiums are addressed. In particular, the study highlights institutional weaknesses in Icelandic party politics as potential causes of positive real party premiums. The results of the study do not undermine the hypothesis that such real income premiums existed in the period of analysis.